Percutaneous sclerotherapy of liver and renal cysts, comments on the EFSUMB guidelines - Dietrich, C. F.; Chiorean, L.; Potthoff, A.; Ignee, A.; Cui, X.; Sparchez, Z. (Zeitschrift für Gastroenterologie, 2016)
Cystic lesions in the liver and kidneys are common incidental findings. They are generally benign and require no treatment. They can appear sporadically or as part of a syndrome, and are characterised by their anechoic structure and posterior enhancement in ultrasound imaging. Increased size, haemorrhage or infection of a cyst can lead to development of symptoms. Along with surgical options and laparoscopic cyst fenestration, ultrasound-guided sclerotherapy of symptomatic cysts represents an effective and safe minimally invasive treatment option.
Keywords: Leber; Richtlinien; Empfehlungen